1998
DOI: 10.1051/aas:1998282
|View full text |Cite
|
Sign up to set email alerts
|

50 μas resolution VLBI images of AGN's at λ3 mm

Abstract: Abstract. We present 15 images from the global mm-VLBI sessions in 1990 April at 100 GHz and 1993 April at 86 GHz. These observations probe the central engines of the 16 observed AGN's with up to 50 µas resolution. Among other sources previously observed with λ3 mm VLBI we present the first λ3 mm maps of 0735+178, 0748+126, 1055+018, 2145+067, and CTA 102, in total we have been able to image 13 out of the 16 observed sources. 6 out of the 13 imaged sources observed exhibit curvature and rapid structural change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…We suggest that the model explored in this paper has applicability to the stationary, unresolved, flat spectrum components revealed with milli-arcsecond VLBI observations, now an established technique for revealing moving and evolving synchrotronemitting jet knots (e.g. Gómez et al 2000;Jorstad et al 2005;Ly et al 2007), and even revealed with global VLBI techniques with 10s of micro-arcsecond resolution (Rantakyro et al 1998).…”
Section: Correlated Radio and Optical/uv Emissionmentioning
confidence: 90%
See 1 more Smart Citation
“…We suggest that the model explored in this paper has applicability to the stationary, unresolved, flat spectrum components revealed with milli-arcsecond VLBI observations, now an established technique for revealing moving and evolving synchrotronemitting jet knots (e.g. Gómez et al 2000;Jorstad et al 2005;Ly et al 2007), and even revealed with global VLBI techniques with 10s of micro-arcsecond resolution (Rantakyro et al 1998).…”
Section: Correlated Radio and Optical/uv Emissionmentioning
confidence: 90%
“…In many subsequent observations of many different objects there has been no direct observational evidence supporting this paradigm and indirect evidence against it, even under the scrutiny of sub-milliarcsec, multi-epoch observations (e.g. Gómez et al 2000;Jorstad et al 2005;Ly et al 2007;Rantakyro et al 1998). There is simply no evidence in support of multiple self-absorbed components which conveniently have successively higher turnover frequencies to explain the overall integrated spectral properties of stationary cores.…”
Section: Beyond Cosmic Conspiracy Theorymentioning
confidence: 99%
“…The emission can be asymmetric due to Doppler shifts associated with rapid rotation (or inflow/outflow) near the black hole. The size of this shadow is within less than a factor of two of the maximum resolution already achieved by sub-mm VLBI (∼ 50µas, Rantakyro et al 1998). It may also be feasible to do polarimetric imaging at mm and sub-mm wavelengths, which would reveal additional effects of strong gravity distortions .…”
Section: Figure 20mentioning
confidence: 91%
“…Sensitive VLBI observations at 86 GHz have been made for several sources, including 3C 111 (Doeleman & Claussen 1997), 3C 454.3 (Krichbaum et al 1995(Krichbaum et al , 1999Pagels et al 2004), NRAO 150 (Agudo et al 2007), NRAO 530 (Bower et al 1997), M87 (Krichbaum et al 2006), 3C 273 and3C 279 (Attridge 2001). In order to increase the number of objects imaged at 86 GHz, four detection and imaging surveys were conducted during the 1990s, with a total of 124 extragalactic radio sources observed (see Beasley et al 1997;Lonsdale et al 1998;Rantakyro et al 1998;Lobanov et al 2000). In these surveys, fringes were detected of 44 objects, but only 24 radio sources have been successfully imaged.…”
Section: Introductionmentioning
confidence: 99%